Manajemen Pembinaan Akhlakul Karimah pada RA Guppi Pekauman Banjarnegara - Umi Arifah; Ika Nura Firmana; Sulis Rokhmawanto; Agus Salim Chamidi (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2022)
The study was conducted to analyze management in the development of morality in RA GUPPI Pekauman, Madukara District, Banjarnegara Regency. The research method was carried out using a qualitative approach to the implementation of education at RA GUPPI Pekauman. The results of the study show that: 1) RA GUPPI Pekauman in planning the management of morality development involves all elements of both madrasas, stakeholders, communities and parents of students who are involved in determining the moral values ​​applied in madrasas contained in the rules; 2) Implementation of the management of moral development of RA GUPPI Pekauman is carried out in teaching and learning activities by integrating character values ​​and moral values ​​in each subject and implemented in extracurricular activities; 3) Evaluation of the management of the moral development of RA GUPPI Pekauman is carried out by making evaluation instruments, recording the achievement of indicators, and conducting analysis and follow-up.